Antioxidant capacity of mango kernel powder extract by different extraction Techniques (Research, Society and Development, 2021)
The mango is a widely cultivated fruit in the world, whose industrial processing generates waste, which are rich in phenolic compounds. Thus, the present work aimed to study the use of mango kernel to obtain extracts with antioxidant activity by applying extraction techniques such as soxhlet system, maceration and ultrasound-assisted, using different solvents. To obtain the flour, the almonds were dried by forced air circulation at 60 ºC. The extracts obtained were evaluated by the yield of the extraction process, total phenolic content (TFT) using the Folin-Ciocalteu method and antioxidant activity (AA) by the ABTS and DPPH free radical methods. Regarding the extract yield, the extraction method by Soxhlet with ethanol showed the best performance when compared to the others (18.78%), because ethanol is more polar than hexane and ethyl acetate. As for the TFT, the maceration method using ethanol showed 451.32 mg EAG/g as the best result, since it is a method that does not use heating. For antioxidant activity by ABTS and DPPH, the values obtained were 2727.23 mM TEAC/g and 3198.58 mM TEAC/g, respectively, for extracts obtained through the maceration technique with ethanol, having the best performance in capturing free radicals. Thus, the mango agroindustrial residue is an interesting co-product to be reused, in order to reduce the inadequate disposal, and replace synthetic antioxidants in the industry, as well as in the preparation of functional foods.